PENGARUH LEVERAGE, ACCOUNTING CONSERVATISM TERHADAP EARNINGS QUALITY DENGAN FIRM SIZE SEBAGAI MODERASI - Metta S, Irene; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2024)
The aim of this research to show empirical evidence the effect of leverage, accounting conservatism on earnings quality and to obtain that firm size moderates the effect of leverage on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange. This research used 70 manufacturing companies selected by using purposive sampling and total of data are 280 for four years. The application for processed the research data by using Eviews application version 12 and Microsoft Excel 2019. The results of this research showed that all independent variables have a simultaneous effect on earnings quality and the partial test showed that leverage has positive and significant effect on earnings quality, accounting conservatism has positive and significant effect on earnings quality, and firm size is able to moderate the effect of leverage on earnings quality.